Tutor-Marked Assignments: Evaluation of Monitoring in India - Ramesh C. Sharma; Mohana Kumar Rajesh (Centre National d'Enseignement à Distance, 2007)
This article examines the practical aspects of assignment evaluation performed by distance education tutors at Indira Gandhi National Open University (IGNOU). The optimal aspects of assignment evaluation are examined in this article. Of interest is the degree of discrepancy as observed in the experimental group vis-à-vis the ideal concepts. The study takes into consideration, all possible divisions in the experimental group, specifically age, gender and programmes of study. Our findings revealed that a properly structured and periodically repeated training programme can reduce the extent of non-teaching comments among distance education tutors. First publication : http://www.asianjde.org/2007v5.3.Sharma.Abstract.html